(untitled) (Revista de História da UEG (REVHIST), 2020)
This article purpose is to analyze the female cartomancers’ actuation in Rio de Janeiro during the 1860s, comprehending their activities simultaneously as magical and religious practices, which were anchored in the period’s social context and as an opportunity to acquire some earning to guarantee their daily expenses management or to complement their income. Therefore, editions of journals that circulated during the period analyzed were investigated in order to observe how those women were inserted into the Rio de Janeiro’s society during the ninetieth century’s latter half, how they developed strategies to promote their services, concomitantly creating a representation about themselves, and in which type of questions those cartomancers acted. Keywords: Cartomancy. Women. 19th Century. Rio de Janeiro.